A method for preparing lead oxide powder containing barium element using lead alloy

By preparing lead-barium binary alloys and preparing lead oxide powders containing barium elements in the lead recycling industry chain, the problem of unstable performance of lead-acid batteries under low temperature conditions is solved, and the battery's low temperature resistance performance is improved and the cycle life is extended.

CN118684264BActive Publication Date: 2025-03-14TIANNENG BATTERY GROUP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411132866.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-03-14
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

Existing lead-acid batteries exhibit unstable low-temperature performance under low temperature conditions, and barium sulfate is prone to agglomeration during the paste, resulting in uneven battery performance and affecting the cycle life of the battery.

Method used

By not extracting barium elements in the lead recovery industry chain, a lead-barium binary alloy is prepared, and a lead oxide powder containing barium elements is prepared through process control, which is used to prepare negative lead paste for low-temperature resistant lead batteries.

Benefits of technology

This method effectively improves the low-temperature performance and cycle life of lead-acid batteries, ensures the battery's retention ability under low temperature conditions, and reduces the loss of barium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for preparing lead oxide powder containing barium element by using alloy lead, and belongs to the technical field of lead storage battery production. The invention prepares PbO powder containing barium element by preparing lead-barium alloy and using the alloy through process control. By using the powder and paste, the lead powder has very good dispersion performance, is not easy to agglomerate, and the battery batch consistency is very ideal. At the same time, the introduction of barium element is realized. Moreover, the barium element introduced in this way is not easy to separate from the active material during the cycle because it is embedded in the PbO crystal structure, which delays the passivation process of the negative electrode. During the entire life, the initial low temperature performance of the battery and the low temperature retention ability during the cycle can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid battery production, and in particular relates to a method for preparing lead oxide powder containing barium element by using alloy lead. Background Art

[0002] For lead-acid batteries used in electric bicycles, low-temperature capacity is its key performance indicator, especially the ability to maintain low temperatures during use, which determines the user's reputation for product quality. In order to improve the low-temperature performance of the battery, expander materials such as lignin, carbon materials and barium sulfate are added to the negative electrode formula. The purpose is to maintain the developed specific surface area structure of the negative electrode active material. The density of lignin and carbon materials is quite different from that of lead powder. Lead powder is also sticky and easy to agglomerate. Barium sulfate is a type of inorganic additive material. Barium sulfate and lead sulfate have similar lattice parameters and are isomorphous substances. There is highly dispersed barium sulfate in the negative electrode active material, which can serve as the crystallization center of lead sulfate during discharge. Since lead sulfate can be crystallized on isomorphous barium sulfate, there is no need to form lead sulfate crystal nuclei, so the supersaturation required for the formation of crystal nuclei will not be generated. The lead sulfate generated under low supersaturation conditions is loose and porous, which is conducive to the diffusion of sulfuric acid. The active material is not covered by the lead sulfate passivation layer, which delays the passivation of the plate. This is closely related to the battery's ability to maintain low temperatures.

[0003] During the barium sulfate paste making process, first of all, the dispersion effect determines the performance of the battery. During the paste making stage, it is also easy to agglomerate, resulting in uneven addition. Secondly, the size of barium sulfate particles also has a great influence on battery performance. Different batches of barium sulfate often have different performances due to uneven particle sizes. Finally, in the process of participating in the construction of the negative electrode active material structure, barium sulfate is continuously precipitated and embedded because it is an inert material. With the formation and recycling, there will be a continuous loss of barium sulfate, resulting in local passivation of the negative plate, reducing the low-temperature performance of the battery. With the recycling, the low-temperature performance gradually decreases.

[0004] In the existing waste battery recycling system, barium will be extracted after the batteries are recycled and smelted. On the battery manufacturing side, as mentioned earlier, because it will have a key impact on battery performance, barium needs to be added to the battery in the form of barium sulfate.

[0005] For example, the patent application with publication number CN110649345A discloses a method for recycling waste lead paste of lead-acid batteries and the application of the recycled materials. The method for recycling waste lead paste of lead-acid batteries comprises the following steps: (1) crushing the waste lead paste with a hammer mill to a particle size of 5 μm-10 μm; (2) sintering the waste lead paste crushed in step (1) to prepare the additive 4BS-BaPbO3; (3) grinding the additive 4BS-BaPbO3 obtained in step (2) to a fineness of 1 μm-5 μm; (4) adding the additive 4BS-BaPbO3 ground in step (3) to the positive lead paste at 1%-8% of the weight of the positive lead powder. The method of the invention recycles the waste lead paste in the production process of lead-acid batteries, and prevents the barium sulfate in the waste lead paste from entering the positive lead paste and affecting the performance of the positive electrode plate by converting barium sulfate into barium lead acid. Summary of the invention

[0006] Based on the deficiencies in the prior art, the present invention provides a method for preparing lead oxide powder containing barium element by using alloy lead. The present invention starts from the entire lead recovery industry chain. The barium element is not extracted, and the recycled lead is only subjected to relatively low-cost impurity removal and purification processes to obtain lead-barium alloy. The alloy is used to prepare PbO powder containing barium element through process control. The powder can be used to prepare low-temperature resistant lead-acid batteries.

[0007] The specific technical solutions of the present invention are as follows:

[0008] The present invention provides a method for preparing lead oxide powder containing barium element by using alloy lead, wherein the alloy lead is recovered from lead-acid batteries, and the lead oxide powder containing barium element is used as a raw material for low-temperature resistant lead-acid batteries. The method comprises the following steps:

[0009] (1) In the lead-acid battery recycling process, barium is not removed during the lead recovery and smelting stage, and lead-barium binary alloy is prepared through impurity removal and purification processes;

[0010] (2) melting the lead-barium binary alloy obtained in step (1) into a liquid state at a melting temperature of 450° C. to 490° C.;

[0011] (3) pulverizing the liquid lead-barium binary alloy obtained in step (2) to obtain a powder, wherein the temperature is controlled at 450° C. to 490° C. during the pulverizing process;

[0012] (4) After the powder obtained in step (3) is crushed and screened, the powder enters a powder bin for collection to obtain the lead oxide powder containing barium.

[0013] Preferably, the ratio of lead to barium in the lead-barium binary alloy is regulated according to the formula for preparing the negative electrode plate of the low-temperature resistant lead-acid battery;

[0014] The content of barium in the lead-barium binary alloy is not less than 1.0%. According to the embodiment of the present invention, the content of barium in the lead-barium binary alloy is between 1.0% and 1.2%, but is not limited thereto.

[0015] Specifically, in step (2), the melting temperature is 485°C.

[0016] Preferably, in step (3), the temperature is controlled at 470°C-490°C during the powder making process. The powder obtained after primary oxidation in the powder making furnace is irregular lead oxide powder;

[0017] Specifically, in step (3), a powder making furnace is used for powder making. The powder making furnace is preheated before the liquid lead-barium binary alloy flows in. The preheating temperature is set to 450°C. The powder making furnace does not need to be heated during the powder making stage, and the temperature in the powder making furnace is controlled within the powder making temperature range during the powder making process.

[0018] Specifically, during the powder making process, the temperature of the powder making furnace is controlled by controlling the speed of the incoming air; when the temperature of the powder making furnace cannot be controlled by controlling the speed of the incoming air, the speed at which the liquid lead-barium binary alloy flows into the powder making furnace is reduced.

[0019] Preferably, during the powder making process, when the temperature in the powder making furnace is lower than 450°C, air is introduced at a rate lower than 8 L / min; when the temperature in the furnace is maintained at 450°C-490°C, air is introduced at a rate not lower than 8 L / min; when the temperature in the furnace rises sharply to above 490°C, the air introduction rate continues to be increased. When the temperature of the powder making furnace cannot be controlled, in addition to controlling the air introduction rate, the rate at which the liquid lead-barium binary alloy flows into the powder making furnace is reduced by half.

[0020] In step (4), the irregular lead oxide powder is crushed and then screened by a secondary cyclone separator and a bag filter pipeline to obtain lead oxide powder without obvious large blocks, and the powder enters a powder bin for collection;

[0021] After the powder is placed in the powder bin for 48 hours, it is screened through a 200-mesh sieve. The screened finished product is transported to the storage bin through a secondary cyclone separator and a bag dust collector pipeline for storage and use in production;

[0022] Control the temperature of the lead melting furnace and the air flow rate of the powder making furnace to achieve temperature control in the furnace. Prepare a PbO powder embedded with the key element barium, the oxidation content of the powder does not exceed 80%, and the mass percentage of β-PbO in the powder is preferably controlled within the range of 20% to 30%, and the α-PbO / β-PbO ratio is controlled within the range of 1.5 to 3.2.

[0023] The invention also provides application of lead oxide powder containing barium element prepared by the method in preparing low temperature resistant lead storage battery. Lead oxide powder containing barium element is used for preparing negative electrode lead paste.

[0024] The invention also provides a negative electrode plate coated with a negative electrode lead paste made of lead oxide powder containing barium element prepared by the method.

[0025] The invention also provides a low temperature resistant lead storage battery, comprising the negative electrode plate.

[0026] Specifically:

[0027] During the paste mixing stage, the powder is automatically weighed according to the production plan, and the remaining additive materials, including fiber, lignin, etc., are also added in corresponding proportions. There is no need to add additional barium-containing additive materials; the entire paste mixing process does not require targeted adjustments; the entire curing process does not require targeted adjustments; during the formation stage, there is no need to increase the formation power.

[0028] Beneficial effects of the present invention:

[0029] The present invention prepares a lead-barium alloy, adopts the alloy, and prepares a PbO powder containing the barium element through process control. By using the powder and paste, the lead powder has very good dispersion performance, is not easy to agglomerate, and the battery batch consistency is very ideal. At the same time, the introduction of the barium element is achieved. Moreover, the barium element introduced in this way is embedded in the PbO crystal structure and is not easy to separate from the active material during the cycle process, which delays the passivation process of the negative electrode. During the entire life span, the initial low-temperature performance of the battery and the low-temperature retention ability during the cycle process can be improved. DETAILED DESCRIPTION

[0030] Example 1

[0031] Waste batteries are recycled, crushed, smelted, purified and impurity-removed, and the element ratio is controlled to prepare an alloy with the composition of each element being 99.0% Pb-1.0% Ba. The alloy lead is sent to the lead melting furnace for melting through a transmission belt. The melting furnace is heated to 450°C. After the alloy lead bars are added, the temperature drops and the lead melting furnace begins to heat up. The process temperature is controlled not to exceed 490°C and is finally maintained at 485°C. The alloy lead is melted into liquid and the lead liquid is stirred. Lead ingots are sampled from three different positions of the lead pot for alloy spectral analysis to confirm the burning loss of the alloy elements, as shown in Table 1.

[0032] Table 1 Alloy spectrum (1)

[0033]

[0034] From the analysis of the spectral results in Table 1, after the alloy lead strip was melted, no large amount of lead slag appeared on the surface of the lead furnace. Within the temperature control range, there was no obvious burning of the elements, which basically remained close to the alloy lead strip.

[0035] No abnormal situation occurred when using the lead liquid to make powder.

[0036] Example 2

[0037] Waste batteries are recycled, crushed, smelted, purified and impurity-removed, and the proportion of elements is controlled to prepare an alloy with the composition of each element being 99.2% Pb-0.8% Ba. The alloy lead is sent to the lead melting furnace for melting through a transmission belt. The melting furnace is heated to 450°C. After the alloy lead bars are added, the temperature drops and the lead melting furnace begins to heat up. The process temperature is controlled not to exceed 490°C and is finally maintained at 485°C. The alloy lead is melted into liquid and the lead liquid is stirred. Lead ingots are sampled from three different positions of the lead pot for alloy spectral analysis to confirm the burning loss of alloy elements, as shown in Table 2.

[0038] Table 2 Alloy spectrum (2)

[0039]

[0040] According to the analysis of the spectral results, after the alloy lead bar was melted, no large amount of lead slag appeared on the surface of the lead furnace. Within the temperature control range, there was no obvious burning of the elements, which basically remained close to the alloy lead bar.

[0041] When the lead liquid is used for powder making, the fluidity of the lead liquid is poor, and the powder making efficiency is reduced by about 13% compared with Example 1.

[0042] Example 3

[0043] Waste batteries are recycled, crushed, smelted, purified and impurity-removed, and the proportion of elements is controlled to prepare an alloy with the composition of each element being 99.5% Pb-0.5% Ba. The alloy lead is sent to the lead melting furnace through a transmission belt for melting. The melting furnace is heated to 450°C. After the alloy lead bars are added, the temperature drops and the lead melting furnace begins to heat up. The process temperature is controlled not to exceed 490°C and is finally maintained at 485°C. The alloy lead is melted into liquid and the lead liquid is stirred. Lead ingots are sampled from three different positions of the lead pot for alloy spectral analysis to confirm the burning loss of alloy elements, as shown in Table 3.

[0044] Table 3 Alloy spectrum (3)

[0045]

[0046] According to the analysis of the spectral results, after the alloy lead bar was melted, no large amount of lead slag appeared on the surface of the lead furnace. Within the temperature control range, there was no obvious burning of the elements, which basically remained close to the alloy lead bar.

[0047] When the lead liquid is used for powder making, the fluidity of the lead liquid is poor, and the efficiency of powder making is reduced by about 30% compared with Example 1.

[0048] Example 4

[0049] After the waste batteries are recycled, crushed, smelted, purified and impurities removed, the proportion of elements is controlled and the alloy is prepared. The composition of each element is 98.8% Pb-1.2% Ba. The alloy lead is sent to the lead melting furnace for melting through a transmission belt. The melting furnace is heated to 450°C. After the alloy lead bars are added, the temperature drops and the lead melting furnace begins to heat up. The process temperature is controlled not to exceed 490°C and is finally maintained at 485°C. The alloy lead is melted into liquid and the lead liquid is stirred. Lead ingots are sampled from three different positions of the lead pot for alloy spectral analysis to confirm the burning loss of alloy elements, as shown in Table 4.

[0050] Table 4 Alloy spectrum (4)

[0051]

[0052] According to the analysis of the spectral results, after the alloy lead bar was melted, no large amount of lead slag appeared on the surface of the lead furnace. Within the temperature control range, there was no obvious burning of the elements, which basically remained close to the alloy lead bar.

[0053] No abnormal situation occurred when using the lead liquid to make powder.

[0054] Example 5

[0055] The powder making furnace is preheated, the temperature in the furnace is maintained at 450°C, the high-speed centrifugal stirring and rotation is turned on, the negative wind pressure is turned on, the lead liquid in Example 1 is selected, and it begins to flow into the powder making furnace. At the same time, air is introduced at a rate of 8L / min, and the temperature in the furnace begins to gradually rise. The temperature reaches 470°C, and air is introduced at a rate of 10L / min, and the temperature slowly decreases. The temperature in the furnace is maintained in the range of 450°C to 470°C, and the flow rate of the lead liquid is maintained. After the powder making, crushing and screening processes, the powder enters the powder bin for collection. After cooling, 3 samples are sampled for XRD testing according to the feeding time sequence of the powder bin. The results are shown in Table 5.

[0056] Table 5 Powder XRD (1)

[0057]

[0058] After XRD results detection, the measured powder is mainly composed of α-PbO and β-PbO, and the combined content of the two exceeds 70%, the content of free lead exceeds 20%, and the content of the remaining lead tetroxide component is relatively low. Sample #1 is the first feed sample, and sample #3 is the last feed sample. The contents of the three samples are basically close.

[0059] Example 6

[0060] The powder making furnace was preheated, the temperature in the furnace was maintained at 450°C, the high-speed centrifugal stirring and rotation was turned on, the negative wind pressure was turned on, the lead liquid in Example 1 was selected, and it began to flow into the powder making furnace. At the same time, air was introduced at a rate of 8L / min, and the temperature in the furnace began to gradually rise. The temperature reached 490°C, and air was introduced at a rate of 10L / min, and the temperature slowly dropped. The temperature in the furnace was maintained in the range of 470°C to 490°C, and the flow rate of the lead liquid was maintained. After the powder making, crushing and screening processes, the powder was collected in the powder bin. After cooling, 3 samples were taken according to the feeding time sequence of the powder bin for XRD testing. The results are shown in Table 6.

[0061] Table 6 Powder XRD (2)

[0062]

[0063] After XRD results detection, the measured powder is mainly composed of α-PbO and β-PbO, and the combined content of the two exceeds 75%, the content of free lead is less than 20%, and the content of the remaining lead tetroxide component is relatively low. Sample #4 is the first feed sample, and sample #6 is the last feed sample. The contents of the three samples are basically close.

[0064] Example 7

[0065] The powder making furnace was preheated, the temperature in the furnace was maintained at 500°C, the high-speed centrifugal stirring and rotation was turned on, the negative wind pressure was turned on, the lead liquid in Example 1 was selected, and it began to flow into the powder making furnace. At the same time, air was introduced at a rate of 8L / min, and the temperature in the furnace began to gradually rise. The temperature reached 520°C, and air was introduced at a rate of 12L / min, and the temperature slowly decreased. The temperature in the furnace was maintained in the range of 490°C to 510°C, and the flow rate of the lead liquid was maintained. After the powder making, crushing and screening processes, the powder was collected in the powder bin. After cooling, 3 samples were taken according to the feeding time sequence of the powder bin for XRD testing. The results are shown in Table 7.

[0066] Table 7 Powder XRD (3)

[0067]

[0068] After XRD results detection, the measured powder is mainly α-PbO and β-PbO, and the total content of the two exceeds 85%, and the β-PbO content begins to increase, the content of free lead is less than 10%, and the content of remaining lead tetroxide components also begins to increase. Sample 7# is the first feed sample and sample 9# is the last feed sample. At this stage, sample 9#, which entered the powder bin later, showed obvious differences in phase compared with sample 7#. The difference between the powders before and after is not conducive to the consistency of subsequent batteries.

[0069] Example 8

[0070] The powder making furnace was preheated, the temperature in the furnace was maintained at 450°C, the high-speed centrifugal stirring and rotation was turned on, the negative wind pressure was turned on, the lead liquid in Example 4 was selected, and it began to flow into the powder making furnace. At the same time, air was introduced at a rate of 8L / min, and the temperature in the furnace began to gradually rise. The temperature reached 470°C, and air was introduced at a rate of 10L / min, and the temperature slowly dropped. The temperature in the furnace was maintained in the range of 450°C to 470°C, and the flow rate of the lead liquid was maintained. After the powder making, crushing and screening processes, the powder was collected in the powder bin. After cooling, 3 samples were taken according to the feeding time sequence of the powder bin for XRD testing. The results are shown in Table 8.

[0071] Table 8 Powder XRD (4)

[0072]

[0073] After XRD results detection, the measured powder is mainly composed of α-PbO and β-PbO, with a total content of about 60%, the content of free lead is close to 40%, and the content of lead tetroxide is extremely low, almost non-existent. Sample 10# is the first feed sample, and sample 12# is the last feed sample. The contents of the three samples remain basically close.

[0074] From the results, it can be seen that under the same powder making process conditions, the oxidation efficiency decreases significantly with the increase of Ba element content. This type of powder has a low oxidation degree, which is not conducive to battery production.

[0075] Example 9

[0076] The powder making furnace is preheated, the temperature in the furnace is maintained at 450°C, the high-speed centrifugal stirring and rotation is turned on, the negative wind pressure is turned on, the lead liquid in Example 4 is selected, and it begins to flow into the powder making furnace. At the same time, air is introduced at a rate of 8L / min, and the temperature in the furnace begins to gradually rise. The temperature reaches 490°C, and air is introduced at a rate of 10L / min. The temperature slowly decreases, and the temperature in the furnace is maintained in the range of 470°C to 490°C. The flow rate of the lead liquid is maintained. After the powder making, crushing and screening processes, the powder enters the powder bin for collection. After cooling, 3 samples are sampled for XRD testing according to the feeding time sequence of the powder bin. The results are shown in Table 9.

[0077] Table 9 Powder XRD (5)

[0078]

[0079] After XRD results detection, the measured powder is mainly composed of α-PbO and β-PbO, and the combined content of the two exceeds 75%, the content of free lead is less than 20%, and the content of the remaining lead tetroxide component is relatively low. Sample #13 is the first feed sample, and sample #15 is the last feed sample. The contents of the three samples are basically close.

[0080] From the results, it can be seen that compared with Example 8, the oxidation efficiency is significantly improved by adjusting the powder making process, and the oxidation degree of this type of powder meets the requirements of the battery production process.

[0081] Example 10

[0082] The powder making furnace was preheated, the temperature in the furnace was maintained at 500°C, the high-speed centrifugal stirring and rotation was turned on, the negative wind pressure was turned on, the lead liquid in Example 4 was selected, and it began to flow into the powder making furnace. At the same time, air was introduced at a rate of 8L / min, and the temperature in the furnace began to gradually rise. The temperature reached 520°C, and air was introduced at a rate of 12L / min, and the temperature slowly decreased. The temperature in the furnace was maintained in the range of 490°C to 510°C, and the flow rate of the lead liquid was maintained. After the powder making, crushing and screening processes, the powder was collected in the powder bin. After cooling, 3 samples were taken according to the feeding time sequence of the powder bin for XRD testing. The results are shown in Table 10.

[0083] Table 10 Powder XRD (6)

[0084]

[0085] After XRD results detection, the measured powder is mainly α-PbO and β-PbO, and the total content of the two is about 85%, and the β-PbO content begins to increase, the content of free lead is less than 10%, and the content of remaining lead tetroxide components also begins to increase. Sample 16# is the first feed sample, and sample 18# is the last feed sample. At this stage, sample 18#, which entered the powder bin later, showed obvious differences in phase compared with sample 16#. The difference between the powders before and after is not conducive to the consistency of subsequent batteries.

[0086] Embodiment 11

[0087] (1) Preparation of experimental battery #1

[0088] The powder prepared in Example 5 was selected for battery experiment. The lead paste was prepared by vacuum paste machine. The weight of the negative plate powder was 700 kg. A total of 60.2 kg of sulfuric acid (density 1.4 g / cm 3 ), 66.5kg pure water.

[0089] Based on the above existing formula, according to the weight of 700kg lead powder,

[0090] Add 1.4kg lignin, which is produced by Borregaard of Norway and has the brand name VA.

[0091] 0.49 kg of short fibers were added.

[0092] The negative electrode plate is prepared by coating, curing and slicing in the conventional way. The positive electrode plate is the corresponding plate with the same size as the negative electrode. In the positive electrode formula, according to the mass percentage of lead powder, 0.5% antimony trioxide, 0.5% stannous sulfate, and 0.07% short fiber are added. The lead paste is prepared by vacuum and paste. The pure water and sulfuric acid used in the paste process are added in an amount calculated by the mass percentage of lead powder, sulfuric acid, 9.2%, and the density of sulfuric acid is 1.4g / cm 3 (25℃), pure water, 9.3%. After coating, curing and slicing, the positive plate preparation is completed, and the two plates are assembled into a 6-DZF-20 battery.

[0093] (2) Preparation of experimental battery #2

[0094] The powder prepared in Example 6 was selected for battery experiment. The lead paste was prepared by vacuum paste machine. The weight of the negative plate powder was 700 kg. A total of 60.2 kg of sulfuric acid (density 1.4 g / cm 3 ), 66.5kg pure water.

[0095] Based on the above existing formula, according to the weight of 700kg lead powder,

[0096] Add 1.4kg lignin, which is produced by Borregaard of Norway and has the brand name VA.

[0097] 0.49 kg of short fibers were added.

[0098] The negative electrode plate is prepared by coating, curing and slicing in the conventional manner.

[0099] The positive plates from the same batch as those of the 1# experimental battery were used to assemble 6-DZF-20 batteries.

[0100] (3) Preparation of experimental battery #3

[0101] The powder prepared in Example 7 was selected for battery experiment. After the powder was ground, it was stirred in a paste mixer to ensure that the phase composition of the powder was close. The lead paste was prepared by a vacuum paste mixer. The weight of the negative plate powder was 700 kg. A total of 60.2 kg of sulfuric acid (density 1.4 g / cm 3 ), 66.5kg pure water.

[0102] Based on the above existing formula, according to the weight of 700kg lead powder,

[0103] Add 1.4kg lignin, lignin is produced by Borregaard of Norway, brand is VA

[0104] 0.49 kg of short fibers were added.

[0105] The negative electrode plate is prepared by coating, curing and slicing in the conventional manner.

[0106] The positive plates from the same batch as those of the 1# experimental battery were used to assemble 6-DZF-20 batteries.

[0107] (4) Preparation of 4# experimental battery

[0108] The powder prepared in Example 8 was selected for battery experiment. The lead paste was prepared by vacuum paste machine. The weight of the negative plate powder was 700 kg. A total of 60.2 kg of sulfuric acid (density 1.4 g / cm 3 ), 66.5kg pure water.

[0109] Based on the above existing formula, according to the weight of 700kg lead powder,

[0110] Add 1.4kg lignin, which is produced by Borregaard of Norway and has the brand name VA.

[0111] 0.49 kg of short fibers were added.

[0112] The positive plates from the same batch as those of the 1# experimental battery were used to assemble 6-DZF-20 batteries.

[0113] (5) Preparation of 5# experimental battery

[0114] The powder prepared in Example 9 was selected for battery experiment. The lead paste was prepared by vacuum paste machine. The weight of the negative plate powder was 700 kg. A total of 60.2 kg of sulfuric acid (density 1.4 g / cm 3 ), 66.5kg pure water.

[0115] Based on the above existing formula, according to the weight of 700kg lead powder,

[0116] Add 1.4kg lignin, which is produced by Borregaard of Norway and has the brand name VA.

[0117] 0.49 kg of short fibers were added.

[0118] The negative electrode plate is prepared by coating, curing and slicing in the conventional manner.

[0119] The positive plates from the same batch as those of the 1# experimental battery were used to assemble 6-DZF-20 batteries.

[0120] (6) Preparation of 6# experimental battery

[0121] The powder prepared in Example 10 was selected for battery experiment. After the powder was ground, it was stirred in a paste mixer to ensure that the phase composition of the powder was close. The lead paste was prepared by a vacuum paste mixer. The weight of the negative plate powder was 700 kg. A total of 60.2 kg of sulfuric acid (density 1.4 g / cm 3 ), 66.5kg pure water.

[0122] Based on the above existing formula, according to the weight of 700kg lead powder,

[0123] Add 1.4kg lignin, lignin is produced by Borregaard of Norway, brand is VA

[0124] 0.49 kg of short fibers were added.

[0125] The negative electrode plate is prepared by coating, curing and slicing in the conventional manner.

[0126] The positive plates from the same batch as those of the 1# experimental battery were used to assemble 6-DZF-20 batteries.

[0127] (7) Preparation of comparative batteries

[0128] The lead paste was prepared by vacuum paste machine. The lead powder used was produced by conventional Shimadzu powder method. The lead powder weight was 700kg, and 60.2kg sulfuric acid (density 1.4g / cm 3 ), 66.5kg pure water.

[0129] Based on the above existing formula, according to the weight of 700kg lead powder,

[0130] Add 1.4kg lignin, which is produced by Borregaard of Norway and has the brand name VA.

[0131] 0.49 kg of short fibers were added.

[0132] The negative electrode plate is prepared by coating, curing and slicing in the conventional manner.

[0133] The positive plates from the same batch as those of the 1# experimental battery were used to assemble 6-DZF-20 batteries.

[0134] (8) Battery performance testing

[0135] The lead-acid batteries after the formation of the six embodiments and the comparative examples were sampled respectively. In order to verify the consistency of the batteries, 10 were taken respectively, and a two-hour rate normal temperature capacity test was performed in accordance with GB / T22199.1-2017 "Valve-regulated Lead-acid Battery for Electric Power Assisted Vehicles". After the test, all were subjected to -18°C low temperature detection. After the low temperature detection, 3 were taken respectively from each of them, and a single life test was performed in accordance with the environment required by GB / T22199.1-2017, wherein the life test method is as follows:

[0136] Constant current discharge: 10A constant current discharge, until the voltage reaches 10.5V, and then enter the constant voltage and current limiting charging stage;

[0137] Constant voltage and current limiting charging: constant voltage 14.8V, current limiting 10A, charging time limit 5h, to fully charge the battery.

[0138] The above is one cycle, with 100 cycles as a unit. After each unit is completed, charging is completed and a -18°C low-temperature test is carried out in the environment required by GB / T22199.1-2017.

[0139] When the battery discharge time is less than 96 minutes for three consecutive times, the battery is considered to be failed. The three cycles are not added to the number of cycles. After the cycle is completed, a -18℃ low-temperature test is performed in the environment required by GB / T22199.1-2017.

[0140] Table 11 compares the average capacity of seven types of batteries at two-hour rates.

[0141] Table 11 Comparison of normal temperature capacity test

[0142]

[0143] As can be seen from Table 11, at the two-hour rate discharge, 1#, 2# and comparison batteries are close, 5# battery is slightly higher, and 3# battery's capacity decreases each time. 4# battery's room temperature capacity is obviously lower, and 6# battery's room temperature capacity decreases extremely fast. Obviously, these types of batteries have quality defects, and subsequent low-temperature capacity and cycle life have not been further tested.

[0144] After the normal temperature capacity test, 1#, 2#, 5# and comparison batteries, a total of 40, were all tested for -18℃ low temperature capacity. Table 12 shows the comparison results of -18℃ low temperature capacity of the four types of batteries.

[0145] Table 12 Comparison of low temperature capacity (min)

[0146]

[0147] From the test results, the 2# and 5# experimental batteries have the highest low-temperature capacity and the smallest variance value, indicating that the battery consistency is the best. The comparison battery has the lowest low-temperature capacity and poor consistency. Through analysis, the powder used for the negative electrode of the 2# battery is the powder prepared in Example 6, the powder used for the negative electrode of the 5# battery is the powder prepared in Example 9, and the 1# is the powder prepared in Example 5. From the above results, the low-temperature capacity is significantly improved by using the experimental powder, and the low-temperature improvement of the powder in Example 6 is the highest and the consistency is the best.

[0148] After the low temperature capacity test, three batteries with similar low temperature capacity were selected from each of the three types of batteries for a single cycle. After each unit was completed, a low temperature capacity test was performed. After the cycle life was terminated, a low temperature capacity test was also performed. The low temperature average values ​​are shown in Table 13 below:

[0149] Table 13 Comparison of low temperature capacity during the cycle

[0150]

[0151] From the above table, we can see that the cycle life of 1# battery and 2# battery using the experimental powder also increases slightly, and the cycle life of 5# battery using the experimental powder is lower than that of the comparison battery.

[0152] During the cycle process, the low-temperature attenuation of the three batteries using the experimental powders was significantly better than that of the control batteries, indicating that the low-temperature retention capacity of the lead-acid batteries prepared using this type of lead powder has been greatly improved.

Claims

1. A method for preparing lead oxide powder containing barium using lead alloy, characterized in that: The alloy lead is recovered from lead-acid batteries, and the lead oxide powder containing barium is used as a raw material for low-temperature resistant lead-acid batteries, comprising the following steps: (1) In the lead-acid battery recycling process, barium is not removed during the lead recovery and smelting stage, and lead-barium binary alloy is prepared through impurity removal and purification processes; (2) melting the lead-barium binary alloy obtained in step (1) into a liquid state at a melting temperature of 450° C. to 490° C.; (3) pulverizing the liquid lead-barium binary alloy obtained in step (2) to obtain a powder, wherein the temperature is controlled at 450° C. to 490° C. during the pulverizing process; (4) After crushing and screening the powder obtained in step (3), the powder enters a powder bin to collect the lead oxide powder containing barium; the oxidation degree of the lead oxide powder containing barium does not exceed 80%, the mass percentage of β-PbO in the powder is controlled within 20% to 30%, and the ratio of α-PbO to β-PbO is controlled within 1.5 to 3.2; The ratio of lead to barium in the lead-barium binary alloy is regulated according to the formula for preparing the negative electrode plate in the low-temperature resistant lead-acid battery; Among them, the barium content in the lead-barium binary alloy is not less than 1.0%.

2. The method for preparing lead oxide powder containing barium element by using alloy lead according to claim 1, characterized in that: In step (2), the melting temperature is 485°C.

3. The method for preparing lead oxide powder containing barium element by using alloy lead according to claim 1, characterized in that: In step (3), the temperature is controlled at 470°C-490°C during the powder making process.

4. The method for preparing lead oxide powder containing barium element by using alloy lead according to claim 1, characterized in that: In step (3), a powder making furnace is used for powder making. The powder making furnace is preheated before the liquid lead-barium binary alloy flows in. The preheating temperature is set to 450°C. The powder making furnace does not need to be heated during the powder making stage, and the temperature in the powder making furnace is controlled within the powder making temperature range during the powder making process.

5. The method for preparing lead oxide powder containing barium element by using alloy lead according to claim 4, characterized in that: During the powder making process, the temperature of the powder making furnace is controlled by controlling the speed of the air supply; when the temperature of the powder making furnace cannot be controlled by controlling the speed of the air supply, the speed at which the liquid lead-barium binary alloy flows into the powder making furnace is reduced.

6. The method for preparing lead oxide powder containing barium element by using alloy lead according to claim 5, characterized in that: During the powder making process, when the temperature in the powder making furnace is lower than 450°C, air is introduced at a rate lower than 8L / min; when the temperature in the furnace is maintained at 450°C~490°C, air is introduced at a rate not lower than 8L / min; when the temperature in the furnace rises sharply to above 490°C, the air introduction rate continues to increase. When the temperature of the powder making furnace cannot be controlled, the rate at which the liquid lead-barium binary alloy flows into the powder making furnace is reduced by half.

7. Use of the lead oxide powder containing barium element obtained by the method described in any one of claims 1 to 6 in the preparation of low-temperature resistant lead-acid batteries, wherein the lead oxide powder containing barium element is used to prepare negative electrode lead paste.

8. A negative electrode plate, characterized in that: A negative electrode lead paste coated with lead oxide powder containing barium element prepared by the method described in any one of claims 1 to 6.

9. A low temperature resistant lead-acid battery, characterized in that: Comprising the negative electrode plate as claimed in claim 8.

Citation Information

Patent Citations

  • Method of recycling waste lead plaster in production process of lead-acid storage battery and application of recycled material

    CN110649345A

  • Negative plate of battery, preparation method thereof and battery comprising negative plate

    CN102683708A

  • Multi-element alloy of positive electrode plate grid for lead accumulator and preparation method of multi-element alloy

    CN104060122A

  • Method for preparing red lead by using alloy lead

    CN117361610A

  • Positive electrode lead paste of long-life lead storage battery and preparation method of positive electrode lead paste

    CN117558879A